A History of #BCSM and Insights for Patient-Centered Online Interaction and Engagement - Matthew S. Katz; Alicia C. Staley; Deanna J. Attai (Journal of Patient-Centered Research and Reviews, 2020)
Purpose: Participation in cancer support groups can provide a sense of community and may better prepare patients for interactions with their health care team. Online interactions may overcome some barriers to in-person support group participation. #BCSM (breast cancer social media), the first cancer support community established on Twitter, was founded in 2011 by two breast cancer survivors. The aims of this study are to describe the growth and changes in this community and to discuss future directions and lessons that may apply to other online support communities. Methods: Symplur Signals was used to obtain all #BCSM Twitter data from January 1, 2011, to January 1, 2020 (00:00:00 Coordinated Universal Time for both). Hashtag use by selected stakeholder groups, user locations, weekly tweet chat activity, and topics were determined. Results: From year 1 (2011) to year 9 (2019), tweets using the #BCSM hashtag increased by 424%. Tweets by patient advocates increased by 226%, with a peak in 2016. Impressions, a measure of potential tweet views, by patient advocates increased by 517%. Tweets by doctors and nonphysician health care professionals increased by 693%. Weekly #BCSM tweet chat activity peaked in 2013, increasing by 58.1% from 2011. Chat topics have included survivorship, metastatic breast cancer, death and dying, advocacy, and highlights from national breast cancer meetings. Conclusions: #BCSM has experienced tremendous growth since 2011, although there are challenges to community sustainability. The weekly chats, as well as discussions utilizing the hashtag but occurring outside of scheduled chat times, serve as an important resource for patients and offer physicians an opportunity to both support and learn from patients.